Antiproliferative and Antitelomerase Effects of Silymarin on Human Colorectal and Hepatocellular Carcinoma Cells - Rahimi, Daruosh; Sharifi, Roya; Jaberie, Hajar; Naghibalhossaini, Fakhraddin (Planta Medica, 2024)
Silymarin, a widely-used hepatoprotective agent, has shown antitumor properties in both in vitro and animal studies. Currently, there is limited knowledge regarding silymarinʼs antitelomerase effects on human colorectal cancer and hepatocyte carcinoma cells. In this study, we investigated the antiproliferative and antitelomerase effects of silymarin on four human colorectal cancer and HepG2 hepatocyte carcinoma cell lines. The cell viability and telomerase activity were assessed using MTT and the telomerase repeat amplification protocol assay, respectively. We also investigated the effects of silymarin on the expression of human telomerase reverse transcriptase and its promoter methylation in HepG2 cells by real-time RT-PCR and methylation-specific PCR, respectively. Silymarin treatment inhibited cell proliferation and telomerase activity in all cancer cells. After 24 h of treatment, silymarin exhibited IC50 values ranging from 19 – 56.3 µg/mL against these cancer cells. A 30-min treatment with silymarin at the IC50 concentration effectively inhibited telomerase activity in cell-free extracts of both colorectal cancer and hepatocyte carcinoma cells. Treatment of HepG2 cells with 10 and 30 µg/mL of silymarin for 48 h resulted in a decrease in human telomerase reverse transcriptase expression to 75 and 35% of the level observed in the untreated control (p < 0.01), respectively. Treatment with silymarin (10, 30, and 60 µg/mL) for 48 h did not affect human telomerase reverse transcriptase promoter methylation in HepG2 cells. In conclusion, our findings suggest that silymarin inhibits cancer cell growth by directly inhibiting telomerase activity and downregulating its human telomerase reverse transcriptase catalytic subunit. However, silymarin did not affect human telomerase reverse transcriptase promoter methylation at the concentrations of 10 – 60 µg/mL used in this study.
Keywords: Silybum marianum; Asteraceae; Telomerase; hTERT; colorectal cancer cells; hepatocarcinoma cells